Let Us Raise and Clang Our Glasses! Tracing the History of the Student Songs - Žičkienė, Aušra (Tautosakos darbai, 2015)
The article aims at revealing the vitality of the oral cultural pattern as illustrated by the songs spread by perhaps the most literate community – students. The analysis of Lithuanian student songs focuses on two compositions that have been favored by students for quite a long time, travelling between European universities orally (at least in part) and sometimes even radically changing their shape.One of these songs is entitled Krambambuli (that is also the name of a strong liquor). It appeared in Lithuania in relation to the establishment of the student corporations following the German example. Yet among the Lithuanian students during the interwar period not the translated German song grew popular, but its local Lithuanian version. The Lithuanian Krambambuli inherited certain traits not only from its German predecessor, but also from the folkloric variants of the Russian translation, including some peculiarities of both the lyrics and melody, and certain additional features. By way of oral learning, dissemination, and variation this song was popular until the beginning of the 1960s. After Lithuania regained its independence and corporations renewed their activities at the universities, the song Krambambuli started sounding again, but today it cannot be regarded as a popular song. Members of the corporations learn it purposefully, as traditional heritage, which should be preserved and respected. Today Krambambuli seems to have turned into a presentable, “show” composition; it is difficult to say if it is ever going to find its way back into folklore proper again, enriching the treasury of the spontaneously developing folk creativity.Another song, the history of which we also use here as an illustration, is given a provisory title “Let Us Raise and Clang Our Glasses!” according to the prevailing lines of its refrain. Its melody, adapted from an Italian student song of the beginning of the 20th century, travelled to Lithuania via Russia, followed by the lyrics, which in Lithuania, however, was transformed into a patchy medley of unrelated humorous couplets. In Lithuania, this song exists and is learned almost exclusively orally, while its fragments “behave” in the virtual space not unlike the paremias: they are used to season the speech, to illustrate, to accentuate the peculiarity of the situation, or even as punchlines in certain funny situations.The first thing that draws attention when we attempt generalizing the history of the both long-lived student songs in question is the fact that they are male songs; incidentally, this tendency can be observed in the corpus of the student songs even today, although the student community has long ago ceased to be a masculine one. Masculinity, frivolity, beer, youth, love, gaiety – these are the main themes that have perhaps determined the long-lived popularity of the songs in question. However, the analyzed songs are interrelated not only in terms of their themes; they keep balancing on the borderline between cultural layers. Having emerged from the professional compositions, they are likely to be performed onstage, nicely arranged and perfectly intoned by professionally trained choirs. Yet another time the same song can completely adhere to the requirements of the popular scene, readily adapting to the popular taste by flexibly altering its shape and finally sounding in accordance to the requirements of almost the lowest social strata. Nevertheless, the most intriguing is the possibility of discerning the basic principles of folklore in the history of these songs; these principles are essentially similar to those developed by the oral culture in the ancient communities. Songs keep surviving for lengthy periods; they are repeated and in demand, since their texts seem lucid to the majority of the community members. They reflect the prevailing vision of the surrounding world, although their melodies change while crossing different countries and regions: they are adapted or even recreated, because they keep hitting the local filters that censor the song’s expression; these comprise certain pools of the musical forms, intonations and complex figures. The power of these filters may perhaps account for dissemination of certain forms of the musical expression in some areas and their total absence or strong changes in the others. If we add criteria of variation, collectivity, loss of authorship or its assumed irrelevance, and emphasize the importance that these songs acquire in relation to customs and rituals, we can perhaps complete the list of the main principles of folklore that are observed in these hybrid compositions – student songs.The traces of folklore found in the student songs do not mean, however, that these compositions can be considered folklore. Still, the student songs are shaped, sound and leave the living tradition precisely following the laws of the oral cultural pattern, thus “behave” in correspondence to its norms. So, even if today we are surrounded not only by the written, but also by the media culture, the modern community, if it is indeed a living and a self-renewing one, cannot completely discard the patterns of oral culture as well. The songs are an inherent part of such pattern, accompanying various rituals and customs or simply helping to create a happier kind of the daily life and making it meaningful.
Keywords: -